A COMPREHENSIVE REVIEW ON ADULTERATION AND SUBSTITUTION OF CRUDE DRUGS - AGARWAL, PRINCY; GOYAL, ANJU (Asian Journal of Pharmaceutical and Clinical Research, 2021)
Herbs are an effective source of Ayurvedic medicine and other traditional medicines as well as modern medicine. Faced with the challenges of modern medicine, the world is shifting toward Ayurvedic theories of health management. In the treatment of the disease, the use of drugs is not limited. This increases the demand for raw materials exponentially. However, production growth is still linear. Rapid depletion of resources creates major problems. To fill the deficit, advances in adulteration and substitution are becoming more prevalent. This adulteration and substitution are a burning problem in an industry that threatens the integrity of Ayurvedic system of medicine. Imprecise knowledge, misidentification, deforestation, and personal gain have led to adulteration. Therefore, an understanding of all ways of adulteration and substitutions is needed to amend this illegal act and maximize consumer safety. This article focuses on adulteration, its types and various methods of adulteration, as well as the concept of substitution, reasoning, and its types. Attempts have also been made to differentiate these two related terms.